(untitled) (Bangladesh Journal of Pharmacology, 2016)
Phytotherapy is a discipline which is interested in the design, the preparation and the interpretation of structure activity relationship of the natural bioactive molecules. In this context, ethanolic leaves extract of Melia azedarach L. was phytochemically analysed on the bases of HPLC and by GCMS. Extract wase tested for his in vitro antioxidant activities by 1,1-diphenyl-2-picrylhydrazyl (DPPH), H2O2, hydroxyl radical scavenging activity, Ferric Reducing Power (FRP) and Ferrous ion chelating abilities methods. The antioxidant activity of the extract was analyzed simultaneously with their pro-oxidant capacity. The ratio of pro-oxidant to the antioxidant activity (ProAntidex) represents a useful index of the net free radical scavenging potential of the synthesized compounds. Tested extract showed significant antioxidant activity with a moderate ProAntidex. Video clips of Methodology: Ferrous ion chelating ability (FIC) 1 Click to watch Ferrous ion chelating ability (FIC) 2 Click to watch Ferrous ion chelating ability (FIC) 3 Click to watch